1997
DOI: 10.1016/s0895-7061(97)00126-x
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Blood Pressure Monitoring: How Reproducible Is It?

Abstract: We tested the reproducibility of ambulatory blood pressure monitoring (ABPM) by the use of agreement plots. Thirty-two normotensive volunteers underwent ABPM on four separate days (interval 28 days), on the same typical weekday. Sleeping time was restricted to the ABPM nighttime subperiod from 11:00 PM to 7:00 AM. Twenty-four-hour average values-both systolic and diastolic-daytime average values, and nighttime average values, as well as standard deviation (SD) values, were analyzed for differences (analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 18 publications
2
20
1
Order By: Relevance
“…Previously, similar data have been reported in healthy normotensive adults as well as in untreated and treated patients with arterial hypertension [32,[35][36][37][38][39][40][41][42]. In accordance with our results, many studies have shown that ambulatory BP values are more reproducible than office BP values [13,[43][44][45][46].…”
Section: Discussionsupporting
confidence: 92%
“…Previously, similar data have been reported in healthy normotensive adults as well as in untreated and treated patients with arterial hypertension [32,[35][36][37][38][39][40][41][42]. In accordance with our results, many studies have shown that ambulatory BP values are more reproducible than office BP values [13,[43][44][45][46].…”
Section: Discussionsupporting
confidence: 92%
“…Tolerability of the technique has been discussed as a possible limitation, mostly because ABPM could induce modest sleep disturbances. 36 Moreover, there seems to be low individual reproducibility of the circadian profile in BP by repeated ABPM performed on the same patients, 37 although results again show clear advantages of ABPM over office values in terms of reproducibility. 38 Some investigators have attempted to extrapolate the advantages of ABPM in general practice to the diagnosis of hypertension in pregnancy.…”
Section: Discussionmentioning
confidence: 98%
“…Statistical methods used to report reproducibility in ambulatory blood pressure monitoring have been simple correlations, 11,28,30 paired t-tests, 33 or ANO-VA. [31][32][33] Both a nonsignificant paired t-test and an excellent intraclass correlation between trials were used in this study to define reproducibility. The intraclass correlation would establish a significant association between the two trials whereas the nonsignficant paired t-test would confirm no differences between the two trials.…”
Section: Discussionmentioning
confidence: 99%
“…36 Subjects in this study were similar to subjects found in other reproducibility studies. 11,31,32 In addition, the subject sample falls into the blood pressure range that would be expected to lower blood pressure with exercise. 40 Therefore, the subject sample was representative of a normal population of middle-aged Stage I hypertensive individuals and suitable to assess the reproducibility of postexercise ambulatory blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation